Effects of hydrogen enrichment on CH4/Air turbulent swirling premixed flames in a cuboid combustor. (18th March 2020) - Park, Joonhwi; Minamoto, Yuki; Shimura, Masayasu; Tanahashi, Mamoru
Abstract: Effects of H2 -enrichment on structures of CH4 /air turbulent swirling premixed flames affected by high intensity turbulence in a gas turbine model combsutor are investigated by conducting direct numerical simulations. Two stoichiometric mixture conditions, of which volume ratio of CH4 :H2 = 50:50 and 80:20, are simulated by considering a reduced chemistry (25 species and 111 reactions). Results showed qualitatively different flame shapes and reaction zone characteristics between the cases. For the higher H2 -ratio case, the flame is stabilized both in the inner and outer shear layers. For the lower H2 -ratio case, the flame is stabilized only in the inner shear layer and extinction occurs in the outer shear layer. Comparison of the reaction zone characteristics with unstrained and strained laminar flames in phase space showed that H2 mass fraction for the lower H2 -ratio case and reaction rate profiles for both cases deviate from the corresponding laminar values. Analysis of fuel species conservation equation suggests that the turbulent transports are substantially influential to determine local and global flame structures. These findings would be useful for designing practical H2 -enriched gas turbine combustor in the aspect of flame structures under high intensity turbulence. Graphical abstract: Image 1 Highlights: Effects of mixture conditions on CH4 /H2 /Air turbulent swirling premixed flames are investigated. Qualitatively different global flame features between the mixture conditions are observed. The role of H2 in each mixture condition remains unchanged even under intense turbulence. Reaction zone characteristics deviate from unstrained and strained laminar flame profiles. Contributions by convection and diffusion are influential on the local and global flame structures.